To determine the angle of repose as affected by particle size, shape, surface condition and moisture content. - Rao, Lakkoju Sankara (Main Library, IIT (BHU), Varanasi, 2022)
To determine the angle of repose as affected by particle size, shape, surface condition and moisture content. This video shows (a)The determination of the angle of repose of Hard Coke of different sizes on wood and steel surface. (b) The determination of the angle of repose of different raw materials of same size on wood and steel surface. (c) The determination of the angle of repose of Iron ore (-6 +4mm) with moisture content (2%,4% & 6%) on steel surface. PART 1 Introduction PART 2 Angle of repose of Hard Coke of different sizes on wood and steel surface PART 3 Different Raw Materials of same size on Wood & Steel Surface PART 4 Effect of moisture on iron ore(-6+4mm) PART 5 Results & Discussions(-6+4mm)